EFFECT OF A CHAMOMILE AND PEPPERMINT POWDERS MIXTURE ON THE QUALITY INDICATORS OF THE RYE-WHEAT BREAD - I. M. Rusina; I. M. Kalesnik; I. P. Liabetskaya (Современная наука и инновации)
The problem of the quality of bakery products shows that wheat flour does not meet modern requirements in some indicators, which affects the degree of expression of consumer characteristics, the content and bioavailability of biologically valuable substances, shortening the stability of physico-chemical and microbiological indicators of finished products. The tasks of improving the quality of products and the introduction of accelerated technologies in modern dynamic production conditions are solved by using various kinds of baking improvers that have a negative impact on human health. The use of medicinal and spicy-aromatic plants, their ability to synthesize and accumulate at the same time a large number of biologically active substances, is a popular and relevant phenomenon in the bakery industry.